Relasi Sosial Ekonomi Perempuan Pedagang Ikan di Pasar Mare Kabupaten Bone - binti Mohd. Yusof, Masnah; Junaeda, St. (Jurnal Ekonomi dan Riset Pembangunan, 2023)
This study aims to determine the socio-economic relations among women fish traders in Pasar Mare. This study used a qualitative research method which was analyzed and written descriptively. Data collection techniques were collected through observation, interviews, and documentation involving 10 individual informants. The results of the study show that: (1) The reasons for women fish traders in Pasar Mare choosing to trade are economic problems, not having a husband, their own desires, and having supplies to sell; (2) In arranging the time between trading and working women traders here find it not difficult and have arranged their time in such a way, because selling time at the market does not take long so that female traders are able to spend time with their families and do their homework both before and after going to school. market.; (3) The relationship between women fish traders here is going very well, this is due to the attitude of helping each other and the principle that is held that at any time they will need each other. For example, dividing the fish caught in parakka in two, helping to sell fish when traveling for a while or when the merchandise is not sold out and exchanging small amounts of money. Besides that, female fish traders often hold arisan, both among fish traders and other traders.